The Development of Pre-service Teacher Resilience during Internship Programs in an Indonesian Private University - Kusumaningtyas, Brigita Woro Diyatni; Kuswandono, Paulus; Ena, Ouda Teda (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Teacher resilience refers to the ability of teachers to adapt to challenges and overcome difficulties in their professional lives. The debates in literatures have centred around the ideas that resilience is not a static characteristic, but rather a fluid and evolving characteristic that can be cultivated and reinforced through a period of time. Pre-service teachers, especially those engaging in school-based practicums as part of their teacher education, should put significant thought into the identities they cultivate as future educators. This study aims to compare pre-service teachers’ resilience during first and second of their internship at school. The research question deriving from this aim is as follows, “What are the students’ comparative perceptions of their resilience during first and second phase of their internship?  A questionnaire was employed to gather the data needed for the research. The findings show that second phase internship students have greater teacher resilience than the first phase internship students. The differences seen can be linked to a range of reasons, including disparate encounters during the teaching practicum, self-efficacy, social support, and the ability to interpret challenges as prospects for growth. Moreover, it has been found that external factors, such as parental expectations and financial considerations, have a significant impact on the development of teacher identity and passion for the teaching profession.